2016
DOI: 10.7439/ijbar.v7i8.3501
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell granuloma of lower lip: A rare case entity

Abstract: Plasma cell granuloma is a benign non-neoplastic lesion which is described under the pseudo-inflammatory tumor category. The etiologies of this lesion are complex and still remain unclear. It occurs primarily in lungs, but also been reported in other extrapulmonary sites. In oral cavity, plasma cell granuloma is exceedingly rare and present as a rapidly growing mass which show aggressive behavior and mimic a malignant tumor, posing a diagnostic dilemma. Histologically, it is composed of polyclonal plasma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Mostly, they have been recorded as single case reports. Oral plasma cell granuloma has been represented in the tongue, 5 lip, 6 oral mucosa, 1 and gingiva. 7,16 The demographic data analysis of the current study groups of OPCG revealed that the ages were found to range from 11 to 73 years with a mean of 42.40 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly, they have been recorded as single case reports. Oral plasma cell granuloma has been represented in the tongue, 5 lip, 6 oral mucosa, 1 and gingiva. 7,16 The demographic data analysis of the current study groups of OPCG revealed that the ages were found to range from 11 to 73 years with a mean of 42.40 years.…”
Section: Discussionmentioning
confidence: 99%
“…3 The occurrence of PCG in the head and neck region is also rare. Oral plasma cell granuloma has been reported to be rarely seen in the oral cavity, as a single unilateral swelling seen primarily on the periodontal tissue, mainly the gingiva, 4 followed by the tongue, 5 lips, 6 buccal and oral mucosa. 1 These lesions have been observed to have no gender predilection and might occur at any age.…”
Section: Introductionmentioning
confidence: 99%